Property Taxation, Local Labor Markets and Rental Housing - Max Löffler; Sebastian Siegloch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Although being heavily analyzed and discussed, there is neither a theoretical nor an empirical consensus on the incidence of the property tax in rental markets. In this paper, we suggest a novel theoretical approach by introducing property taxation into a Rosen-Roback type local labor market model. Besides the standard relative elasticity result, we find that the tax incidence depends on location preferences. The advantageous institutional setting of property taxation in Germany enables us to test our theoretical predictions and provide a clean estimate of the tax incidence using a non-parametric event study research design. Using a panel of roughly 540 communities over up to 20 years, we show that in the short run, the incidence is borne by landlords since housing supply is inelastic. As housing supply becomes more elastic over time, landlords are able to shift the burden onto tenants. After six years, net rents are on the pre-reform level, implying full shifting of the tax.
Keywords: H22; H71; R31; 330